Anti-resonant based nested terahertz fiber design for illicit drugs detection - Shaymaa Riyadh Tahhan; Hadeel K. Aljobouri; Baraa Riyadh Altahan (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Anti-resonant hollow-core fibers (AR-HCFs) have gotten a lot of interest lately because of their potential uses in different medical sensing applications. In this work, an anti-resonant THz fiber (ATF) biosensor is implemented to check for illicit drugs and identify them at airport borders. Three different unlawful medicines have been chosen for the proposed design, Cocaine, Amphetamine, and Ketamine. A novel hollow-core anti-resonant fibers (HC-ARF) Matryoshka shape sensor has been designed for detecting the illegal drugs. The proposed design shows a robust sensitivity ranging from 99.8-99.9% and shallow confinement losses compared to other articles in the same field, as the higher losses are 9.3×10-4 dB/m with cocaine. Bending loss lessens as the bending radius rises while it is still below 1 dB/cm for radius more than 10 cm. The numerical simulation outcomes displayed that the designed HC-ARF has 0.0643±0.0238 ps/THz/cm flat dispersion at 0.6-2 THz. As the first application in this field, this work will be the first published in the literature.